ETHINIC POLITICY ON NATION BUILDING IN SOUTH SUDAN - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Globally, some progress is being made towards achieving the MDGs, but societies affected by ethnic politics. In other word ethnic politics” refers to a situation in which politicians tend to mobilize support on the basis of an appeal to ethnic identity and people tend to support leaders from the same ethnic group. Ethnic politics is often regarded as a problem when different groups come to see each other as competitors for power and when members believe that they will be excluded from the benefits of state assistance and protection if one of their own is not in power. The reason is that such politics often promotes interethnic tension and violence, leading many to argue that ethnic politics needs to be eradicated or managed through tailored institutional arrangements.